STRUCTURAL FUNCTIONAL MODEL OF ACADEMIC STAFF INTERACTION WITHIN A UNIVERSITY COMPLEX - N. V. Silkina; N. O. Vaganova (Образование и наука)
The research analyzes the possibility of coordinated activity of academic staff affiliated to secondary and higher educational institutions within a university complex. The applied methods integrate the analysis of regulatory documents and cooperation expertise of academic staff along with general modeling methods based on the structural and functional approach. The research outcomes reveal the spheres and types of academic staff interaction at various educational levels; the principles and conditions of the interaction in question being defined. The authors demonstrate a structural functional model, determining the organizational and professional aspects, as well as the results of academic staff interaction within the university complex. Implementation of the given model can facilitate the effective integration of split-level educational organizations into the university complex structure.